Gendering religion and politics: untangling modernities - Hertsog, Ḥanah; Herzog, Hanna; Braude, Ann (Palgrave Macmillan, 2009)
Nativism and the politics of gender in Catholicism and Islam / Jose Casanova -- Imagined communities: state, religion, and gender in Jewish settlements / Hanna Herzog -- Contemporary American Catholicism and the challenge of gender equality / Mary C. Segers -- From the Moabite Ruth to Norly the Filipino: intermarriage and conversion in the Jewish nation state / Daphna Hacker -- Seeking recognition: women's struggle for full citizenship in the community of religious worship / Pnina Lahav -- "Subway women" and the American near east relief in Anatolia, 1919-1924 / Anat Lapidot-Pirilla -- Global sisterhood: transnational perspectives on gender and religion / Gertrud Huwelmeier -- Feminism, democracy, and empire: Islam and the war on terror / Saba Mahmood -- Patriarchal ecumenism, feminism, and women's religious experiences in Costa Rica / Elina Vuola -- The boundaries of liberation, the chains of freedom: urban women in 1960s Egyptian popular cinema / Shmulik Bachar -- Language, gender, and power in Morocco / Fatima Sadiqi